DEVELOPMENT OF ARABIC TENSE MODULE IN LEARNING WRITING SKILLS AT FITK UIN MALANG - Prasetiyo, Agung; Fitriani, Ismatul Hidayah; Adlani, Fitroh (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Arabic learning continues to develop, starting with Syauqi Dhoif, Amin al-Khuli, Ibrahim Musthofa, Abdurrahman al-Ayyubi, Muhammad Abd Sattar and Mahdi al-Makhzumi and even Tammam Hassan. The study of nahwu taught still has many problems, especially students find it difficult to understand Arabic because their understanding is very low in the basic concepts of nahwu. Apart from this, there is one important study that many people still don't know, namely tenses. In Arabic, tenses are commonly referred to as epochs ( زمن ). Based on the experience of researchers while teaching Maharah al-Qiraah and Maharah al-Kitabah in the last two years, it can be explained that many Arabic Language Education students make mistakes in making Arabic sentences, for example using idioms, hamzah qotho' and washol and so on. Even a survey conducted by researchers this semester, not a single student knows that Arabic has 16 tenses similar to English. Seeing the phenomenon above, according to the researcher, it is necessary to conduct development research in the form of making modules on Arabic tenses. The aim is to fill the gaps in studies in the field of Arabic tenses. From the results of this research, it can be concluded that the module development with R&D research is expected to be able to provide solutions in learning maharah kitabah. The module has been tested for validity by validators of learning experts and media experts. The results of the learning and media expert validators got an average validation score of 80%. Based on the data from the validation results, the module is valid and can be used in the learning process. Based on the development process and the results of the module trial, it meets the good criteria, and can add to the references of students studying maharah kitabah.